2021
DOI: 10.1038/s41419-021-03557-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cullin-5 neddylation-mediated NOXA degradation is enhanced by PRDX1 oligomers in colorectal cancer

Abstract: NOXA, a BH3-only proapoptotic protein involved in regulating cell death decisions, is highly expressed but short-lived in colorectal cancer (CRC). Neddylated cullin-5 (CUL5)-mediated ubiquitination and degradation of NOXA is crucial to prevent its overaccumulation and maintain an appropriate action time. However, how this process is manipulated by CRC cells commonly exposed to oxidative stress remain unknown. The peroxiredoxin PRDX1, a conceivable antioxidant overexpressed in CRC tissues, has been shown to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Moreover, targeting peroxiredoxin-1 is considered as one of the novel strategies for treatment of colorectal cancers [32]. Recently it has been reported that, to overcome resistance to DNA-damaging agents like etoposide, targeting peroxiredoxin-1 could be a beneficial strategy [33]. As observed in the present study, action of Polyphyllins PD and PII in downregulating the key molecule peroxiredoxin-1 could be employed to achieve this novel treatment option.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, targeting peroxiredoxin-1 is considered as one of the novel strategies for treatment of colorectal cancers [32]. Recently it has been reported that, to overcome resistance to DNA-damaging agents like etoposide, targeting peroxiredoxin-1 could be a beneficial strategy [33]. As observed in the present study, action of Polyphyllins PD and PII in downregulating the key molecule peroxiredoxin-1 could be employed to achieve this novel treatment option.…”
Section: Discussionmentioning
confidence: 57%
“…The activation of mitochondrial and intrinsic pathways by NOXA is critical for the survival of cancer cells. Xu and his team have shown that the neddylation and ubiquitination complexes of UBE2F–Cul5–RBX2 and UBE2M–Parkin/DJ-1 enzymes regulate apoptosis from NOXA turnover . First, UBE2F, one of two neddylators of the ubiquitin-conjugated enzyme (E2), collaborates with RBX2 serving as the E3 neddylator, which initiates Cul5 neddylation around the triplet of a lysine residue (Lys724) .…”
Section: Some Common Substrates Of Cul5mentioning
confidence: 99%
“…Thus, in CRC PRDX1 is essential for maintaining intracellular homeostasis by strengthening te UBE2F–Cul5-mediated degradation of NOXA, as shown by CRC cells’ resistance to etoposide therapy. These results suggest that targeting PRDX1 may be a viable approach to overcoming CRC DNA damage resistance …”
Section: Cullin-5 Targeting For Therapeutic Purposesmentioning
confidence: 99%
See 2 more Smart Citations